2019
DOI: 10.22159/ijcpr.2019v11i4.34948
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Formulation and Characterization of Herbosome Complex

Abstract: The major amount of active constituents comprises in herbal drugs with excellent bioactivity in vitro but less in vivo because of their poor lipid solubility and improper size of the molecules. This results in poor absorption and bioavailability of active constituents from the herbal extract. Herbosome technology enhances the bioavailability of herbal extracts. Herbosome act as the bridge between the novel delivery system and conventional delivery system. It is a complex of natural active ingredients and phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…27 Based on the above study it was concluded that the phytosome formulation of hydroalcoholic extract of Terminalia arjuna and its Tablet formulation improved the bioavailability and may be used as herbal formulation in the treatment of cardiovascular disease for antioxidant activity. 5,8 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Based on the above study it was concluded that the phytosome formulation of hydroalcoholic extract of Terminalia arjuna and its Tablet formulation improved the bioavailability and may be used as herbal formulation in the treatment of cardiovascular disease for antioxidant activity. 5,8 7.…”
Section: Discussionmentioning
confidence: 99%
“…4 Phytosomes is a newly introduced patented technology developed to incorporate the standardized plant extracts or water-soluble phytoconstituents into phospholipids to produce lipid compatible molecular complexes, which improves their absorption and bioavailability. 5,6,7 Phytosome technology has been effectively used to enhance the bioavailability of many popular herbal extracts including milk thistle, ginkgo biloba, grape seed, green tea, hawthorn, ginseng etc and can be utilized for various therapeutic uses or for administration of dietary supplements. The flavonoid and terpenoids components of these herbal extracts lend themselves quite well for the direct binding to phosphatidylcholine.…”
Section: Introductionmentioning
confidence: 99%
“…• Herbosomes are also used as an anti-inflammatory, lipolytic, isokinetic, antiedema, cicatrizing, trophodermic, nutraceutical immunomodulator, antioxidant for skin and liver, cardioprotective, anti-wrinkle, and UV protectant [7].…”
Section: Applicationmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) can visualize herbosomes, revealing their internal composition and characteristics, such as morphology, crystallization, stress, and magnetic domains [7].…”
Section: Visualizationmentioning
confidence: 99%
See 1 more Smart Citation